DISTRIBUTION OF PHOSPHORYLASE IN SOME FISH AND SHELL FISH. - MUKUNDAN, M K; ANTONY, P D (Fishery Technology, 2017)
Phosphorylase content m the muscle of some fish andshell fish were estimated. Jew fish (Johnius duss~uneri) and 'seanaran' (Penaeus indicus) recorded the highest enzyme contentamong the fish and shell fish studied. As phosphorylase is thekey enzyme in glycogenolysis, which is the energy source offish for muscular activity, the possible role of phosphorylasecontent as an index of muscular capacity and post-mortemautolysis is discussed.